Doherty power amplifier - Ding, Wei (2013)
In the design of radio frequency (RF) power amplifier, linearity and efficiency are two essential metrics to be taken into considerations. Typically a RF power amplifier is the most power consumpition block in a communication system. On the other hand, the modern wireless communication standards require a linear power amplifier to achieve linear modulation schemes. It is imperative that the power dissipation of the RF power amplifier is low and its efficiency high. In view of this, the Doherty power amplifier is the interest of this Final Year Project.